Public Service Management Based on Higher Education in the Context of Lecturer Career Development - Wahyuningsih, Sri; Minai, Mohd. Sobri; Shamsuddin, Jauriyah (Universitas Padjadjaran, 2024)
Public Service Management Based on Higher Education in the Context of Lecturer Career Development is a concept that integrates the principles of public service management with higher education to support and improve lecturer career development. The research examines the influence of achievement motivation, competence and performance on the career development of lecturers at private universities in Indonesia, as well as competence as a moderator. A total of 210 questionnaires were distributed to research locations, and 192 (90%) were returned. All data was processed using SEM PLS Smart4. The results show that achievement motivation has a positive and significant effect on lecturer performance. Furthermore, the performance and competence of lecturers will have a positive and significant influence on the career development of private lecturers in Indonesia. However, lecturer competency is not a moderating factor that can increase or weaken the influence of lecturer achievement motivation on performance. Likewise, lecturer competency is not a moderating factor that can increase or weaken the influence of lecturer performance on lecturer career development at private universities in Indonesia.